2011
DOI: 10.1149/1.3552933
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on InP/InAlAsSb/GaAs Metamorphic High Electron Mobility Transistors with a Dual-Composition-Graded InxGa1−xAs1−ySby Channel and Different Schottky-Barrier Gate Structures

Abstract: Device characteristics of InP/In 0.34 Al 0.66 As 0.85 Sb 0.15 /GaAs metamorphic high electron mobility transistors with a dual-compositiongraded In x Ga 1Àx As 1Ày Sb y (x ¼ 0.53 ! 0.63 ! 0.53, y ¼ 0.01 ! 0.02 ! 0.01) channel are comprehensively investigated by forming different Schottky-barrier gate structures of Pt/Au-In 0.34 Al 0.66 As 0.85 Sb 0.15 , Ni/Au-In 0.34 Al 0.66 As 0.85 Sb 0.15 , or Pt/Au-InP, respectively. Superior device gain, current drive, power, noise, and high-frequency characteristics have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Metamorphic devices which have been fabricated on lattice-mismatched substrates include InGaAs/InAlAs HEMTs on GaAs, 3 InGaAs/InAlAs heterojunction bipolar transistors (HBTs) on GaAs, 4 InGaAs/InP HEMTs and HBTs on GaAs, 5 InAlAs photodiodes on GaAs, 6 InAsSb/AlInAsSb light-emitting diodes (LEDs) on GaSb, 7 AlInGaAsSb laser diodes on GaSb, 8 InGaAs/InAlGaAs laser diodes on GaAs, 9 InGaAsSb/InAlAs quantum cascade laser structures on GaAs, 10 and InAlAs solar cells on GaAs. 11 Most work has focused on linearly-graded buffer layers, [2][3][4][5][6][7][8][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] while there have been several reports of the use of step-graded buffer layers 12,[31][32][33][34] or buffer layers with T. Kujofsa continuous, but non-linear grading of composition. 11,[35][36][37] Tersoff's work …”
Section: Introductionmentioning
confidence: 99%
“…Metamorphic devices which have been fabricated on lattice-mismatched substrates include InGaAs/InAlAs HEMTs on GaAs, 3 InGaAs/InAlAs heterojunction bipolar transistors (HBTs) on GaAs, 4 InGaAs/InP HEMTs and HBTs on GaAs, 5 InAlAs photodiodes on GaAs, 6 InAsSb/AlInAsSb light-emitting diodes (LEDs) on GaSb, 7 AlInGaAsSb laser diodes on GaSb, 8 InGaAs/InAlGaAs laser diodes on GaAs, 9 InGaAsSb/InAlAs quantum cascade laser structures on GaAs, 10 and InAlAs solar cells on GaAs. 11 Most work has focused on linearly-graded buffer layers, [2][3][4][5][6][7][8][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] while there have been several reports of the use of step-graded buffer layers 12,[31][32][33][34] or buffer layers with T. Kujofsa continuous, but non-linear grading of composition. 11,[35][36][37] Tersoff's work …”
Section: Introductionmentioning
confidence: 99%
“…For the conventional Schottky-gated HEMTs, the gate leakages are mainly resulted from the current injection through (1) the thermionic emission-enhanced barrier lowering at the Schottky barrier and (2) thermionic trap-assisted tunneling mechanism through the surface states upon the exposed barrier layer between the gate-drain/source regions [9]. In order to enhance the Schottky barrier height, depositing gate metals of high work function on wide-gap barrier layer has been attempted [10]. Other approaches using SiN [11][12] or sulfide [13][14] surface passivation techniques have also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some of InP-based metamorphic transistors grown on low-cost GaAs substrates have been investigated. [7][8][9][10] Previous report had demonstrated that the InGaP buffer could offer better thermal properties resulting in a much smaller thermal resistance in the metamorphic HBTs when compared to the widely used InAlAs metamorphic buffer. 7 In this paper, a new InP/InGaAs co-integrated metamorphic heterostructure bipolar and field-effect transistor (BiFETs) is first demonstrated to exhibit excellent dc performance.…”
mentioning
confidence: 99%